Legal consequences of ngerorod marriage according to marriage law - Aditya Satrya Iswara Taira; Made Warka; Tomy Michael (Technium Social Sciences Journal, 2025)
Marriage or wiwaha for Hindu society has a special meaning and position in human life, namely the beginning of the grehasta level. Marriage is something that is religious (sacred) and obligatory because it is related to a person’s obligation to have children and atone for all their sins and marriage itself is highly respected because it can provide an opportunity for ancestors to incarnate into the world. This marriage aims to live prosperously and happily. Manawadharmasastra explains that there are three purposes of marriage, namely dharmasampatti, praja and rati. Dharmasampatti means together with husband and wife to realize the implementation of dharma), praja means giving birth to offspring and rati means enjoying sexual life and other sensual satisfaction. Legal Consequences of Ngerorod Marriage According to the Marriage Law, important points that need to be considered in relation to the concept of a legal state and the practice of ngerorod marriage in Bali include: Recognition and Protection in Human Rights: A valid marriage according to law must be carried out with the consent both parties. Law No. 1 of 1974 states that marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family based on Almighty God. In this case, human rights such as the right to choose a partner without coercion are highly respected. In the practice of ngerorod, although there seems to be an element of "escape," this process is actually also carried out by agreement of both parties. If both parties agree, then ngerorod can be seen as a form of cultural expression that doesn’t conflict with human rights. However, if there is an element of coercion or disagreement from one of the parties, this can be considered a violation of human rights protected by law.